1987
DOI: 10.1515/znc-1987-11-1225
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Fibrils are a Structural Principle in the Assembly of Interstitial Collagens, Chordae Tendineae Included

Abstract: X-ray diffraction analysis of connective tissue samples, which contain type I and type III collagen shows that twisted collagen fibrils are a general principle of assembly. The occurrence of twisted fibrils in native wet Chordae tendineae, skin and Aorta is combined with a shorter axial periodicity of about 65 nm. This shorter D period is shown to be directly related to the tilt of the molecules, which have to be curved to build-up twisted fibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The effect of helicoidal molecular packing results in the plane of lateral molecular packing to be displaced at an angle from the perpendicular to the fibril axis; i.e., a molecular tilt is introduced (Folkhard et al, 1987). Since the path of the molecules is relative to a common axis, this ensures that the molecular plane is of a constant angle, but the orientation of the plane varies with respect to the fibril axis.…”
Section: Angular Deviation Of Equatorial Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of helicoidal molecular packing results in the plane of lateral molecular packing to be displaced at an angle from the perpendicular to the fibril axis; i.e., a molecular tilt is introduced (Folkhard et al, 1987). Since the path of the molecules is relative to a common axis, this ensures that the molecular plane is of a constant angle, but the orientation of the plane varies with respect to the fibril axis.…”
Section: Angular Deviation Of Equatorial Scatteringmentioning
confidence: 99%
“…Several angles have been reported in the literature for such helicoidal fibrils, with the data coming mainly from electron microscopy: 9° ( Folkhard et al, 1987); 12° (Brodsky and Eikenberry, 1982); 12-13° (Itoh et al, 1996); 14 -17° (Katz and David, 1992); 18° (Ruggeri et al, 1979). X-ray diffraction provides strong evidence for molecular inclination and is capable of estimating the variability of inclination angle within an assembly of fibrils.…”
Section: Angular Deviation Of Equatorial Scatteringmentioning
confidence: 99%
“…There has also been discussion of whether there is a causal relationship between the presence of type III collagen and the twisted arrangement of collagen fibrils or a shorter D period, on the basis of data from the vessel wall and other connective tissues containing type I and type III collagen. However, there is experimental evidence indicating that collagen fibrils of aorta described are also formed in the absence of collagen III, as shown for a patient with type IV Ehlers-Danlos syndrome [41]. Studies on lamprey tissues seem to confirm that tilted fibrils and a reduced D period had already evolved before type III collagen was established during evolution [31].…”
Section: Figure 5 Amino Acid Sequences Of C-telopeptides From α1(i) Amentioning
confidence: 89%
“…Then the tendon exhibits a linear region of elongation that involves either extension of the individual collagen components or relative sliding between them [35,42]. In particular, sincrotone X-ray diffraction studies of the tendon matrix demonstrated that only 40% of tendon elongation occurs at the molecular level, whereas about 60% of tendon extension is due to sliding between one or more of the structural levels of collagen [43,44,45]. Interfibrillar sliding is related to the interfibrillar proteoglycans.…”
Section: Discussionmentioning
confidence: 99%